Pengaruh Kinerja Karyawan Terhadap Kepuasan Anggota Koperasi Pada Koperasi Wiyatamandala (Studi Kasus pada Koperasi Wiyatamadala di Praya, Lombok - Arbain, Lalu Syukroni; Pusparini, Herlina; Jumaidi, Lalu Takdir (Balance : Jurnal Akuntansi dan Manajemen, 2022)
This study aims to find out whether employee performance affects or not the satisfaction of Wiyatamandala cooperative members, and find out how employee performance (service, cooperation, and employee responsibility) affects the satisfaction of Wiyatamandala cooperative members. This type of research is quantitative research. The subject of this study is the Wiyatamandala Cooperative. The object of this study is the member of the wiyatamandala cooperative. The approach used in this study uses a statistical quantitative approach. The main problem studied in this study is the effect of employee performance on the satisfaction of cooperative members in the Wiyatamandala cooperative. The data collection methods in this study were observation, key informants, questionnaires, and documentation. The location of this study is located at SMAN 1 Praya, Praya District, Central Lombok Regency. And process the data using the SPSS application. The results showed that 1) Employee service had no effect and was significant to the satisfaction of the members of the wiyatamandala cooperative, So it can be concluded that Ho was accepted and Ha was rejected. 2) Employee cooperation has an effect and is significant to the satisfaction of the members of the wiyatamandala cooperative, so it can be concluded that Ho was rejected and Ha was accepted. 3) Employee cooperation has an effect and is significant to the satisfaction of the members of the wiyatamandala cooperative, so it can be concluded that Ho was rejected and Ha was accepted. 4) Simultaneously, Service, Cooperation, and Responsibility have an effect and are significant to the satisfaction of wiyatamandala cooperative members, it can be concluded that Ho was rejected and Ha was accepted. The results of the coefficient of determination test showed that employee performance affected the satisfaction of wiyatamandala cooperative members in Praya by 39.5% and the remaining 60.5% was influenced by other variables that were not included in this study.